Analisis implementasi triple bottom line pada program corporate social responsibility di the patra bali resort & villas - I Komang Arif Cahya Pradana; I Komang Mahayana Putra; Wayan Gede Suka Parwita (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This study aims to analyze the implementation of the Triple Bottom Line concept (People, Planet, Profit) in Corporate Social Responsibility (CSR) programs at The Patra Bali Resort & Villas and to identify the challenges faced in its implementation. This research employs a qualitative method with a descriptive approach. The data sources used in this study consist of primary and secondary data. Data collection techniques were conducted through observation, interviews, and documentation involving parties directly engaged in CSR program implementation. Interviews were conducted with the Training Manager, HCBP Hospitality, and CSR program beneficiaries to obtain comprehensive information regarding program implementation.The results indicate that The Patra Bali Resort & Villas has implemented CSR programs that reflect the three dimensions of the Triple Bottom Line. In the People dimension, the company carries out social empowerment programs such as employing persons with disabilities and organizing blood donation activities. In the Planet dimension, the company implements environmental sustainability initiatives, including eco-enzyme waste management and the empowerment of local salt farmer groups. Meanwhile, in the Profit dimension, the company conducts training and certification programs for local tour guides, contributing to long-term economic sustainability.However, several challenges remain, including the absence of structured impact measurement indicators and limitations in continuous monitoring and evaluation of CSR programs.